A Statistical Approach to Alkylation of p-Cresol with Cyclopentanol - Islam, S.T.A.; Alam, M.Z.; Ismail, M.; Galib, M.; Sharif, N.; Saha, M. (Asian Journal of Chemistry, 2010)
A statistical analysis for the yield of alkylation of p-cresol with cyclopentanol in presence of perchloric acid was performed. Design of experiment technique was employed to study the influence of individual effects of the variables and their interactions on yields of alkylation. The effects of temperature, molar ratio of p-cresol to cyclopentanol and amount of perchloric acid were found to be significant. Finally, a mathematical model was developed to predict the theoretical yield of alkylation of p-cresol with cyclopentanol in presence of perchloric acid as a catalyst under any reaction condition.